2009
DOI: 10.1128/aem.02726-08
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Mycobacterium sp. Strain AP1 on the Saturated- and Aromatic-Hydrocarbon Fractions of Fuel Oil in a Marine Medium

Abstract: The pyrene-degrading Mycobacterium sp. strain AP1 grew in nutrient-supplemented artificial seawater with a heavy fuel oil as the sole carbon source, causing the complete removal of all linear (C 12 to C 40 ) and branched alkanes from the aliphatic fraction, as well as an extensive degradation of the three-and four-ring polycyclic aromatic hydrocarbons (PAHs) phenanthrene (95%), anthracene (80%), fluoranthene (80%), pyrene (75%), and benzo(a)anthracene (30%). Alkylated PAHs, which are more abundant in crude oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…As shown in rial), the degradation profiles at day 30 showed that decreases in the amount of aliphatic hydrocarbons had occurred for all the alkanes detected during the incubation with BP crude oil. This result is consistent with early studies with this and other strains of environmental mycobacteria on biodegradation of alkanes (36,(39)(40)(41). Among these identified alkanes, we selected 7 compounds, dodecane (C 12 ), tridecane (C 13 ), hexadecane (C 16 ), icosane (C 20 ), tetracosane (C 24 ), pentacosane (C 25 ), and octacosane (C 28 ), to monitor differences in degradation by the bacterium with time during incubation with BP crude oil.…”
Section: Resultssupporting
confidence: 82%
“…As shown in rial), the degradation profiles at day 30 showed that decreases in the amount of aliphatic hydrocarbons had occurred for all the alkanes detected during the incubation with BP crude oil. This result is consistent with early studies with this and other strains of environmental mycobacteria on biodegradation of alkanes (36,(39)(40)(41). Among these identified alkanes, we selected 7 compounds, dodecane (C 12 ), tridecane (C 13 ), hexadecane (C 16 ), icosane (C 20 ), tetracosane (C 24 ), pentacosane (C 25 ), and octacosane (C 28 ), to monitor differences in degradation by the bacterium with time during incubation with BP crude oil.…”
Section: Resultssupporting
confidence: 82%
“…Notably, these Gammaproteobacteria were not detected in the present work. In PAH‐polluted soils, mycobacteria seem to play a major role in the degradation of pyrene (Kanaly & Harayama, 2000) and pyrene‐degrading mycobacterial strains isolated from oil‐contaminated beaches (Vila et al , 2001) have shown wide degradation capabilities toward a variety of fuel components in marine medium (Vila & Grifoll, 2009). In this study, the detection of an actinobacterial strain belonging to the genus Gordonia as an apparently major component of the pyrene‐degrading community is consistent with a role of actinobacteria in PAH and specifically pyrene removal in coastal environments.…”
Section: Discussionmentioning
confidence: 99%
“…As Mycobacterium is one of the few bacterial genera able to degrade HMW PAHs, and one that is being used in developing remediation strategies for real-world spill mixtures (49,50), understanding the intricacies of PAH mixture degradation by Mycobacterium species is an area of importance in bioremediation research. The aim of this study was to investigate the degradation of PAH substrates by Mycobacterium species and characterize the metabolic changes associated with mixed-substrate antagonism.…”
Section: Discussionmentioning
confidence: 99%